RE:search ABC - Lategan, Laetus (African Sun Media, 2006)
Delivering research outputs has become increasingly important for many students involved in working towards a research degree. RE:search ABC highlights contemporary practices and provides a framework for an up-to-date understanding of the research process and the key issues associated with it. It integrates a number of imperative topics, including the writing of a research protocol, the applying of methodology in research projects, the respective roles of the supervisor and student, the writing of a scientific article and the presenting of research results. The analysis draws upon both theory and real case studies.